Evaluation of wearable system for measuring vital parameters in clinical environment - Koceska, Natasa; Kozolovska, Ivana; Koteska, Bojana; Simjanoska, Monika; Madevska Bogdanova, Ana (My University, 2017)
A continuous monitoring of physiological data is especially important for individuals whose chronic condition includes the risk of sudden acute events. Physiological measurements fluctuate over the course of the day, so a once-daily read-ing might not provide the whole picture. Standard ambulatory systems for monitoring, are not suitable for monitoring over long period of time. The new systems and techniques suitable for hospital environment are investigated over the past years. In this study, we present a wearable system which includes a Zephyr bio-module for measuring patient's vital parameters. Data is collected wirelessly and displayed on mobile device via software. In order to be used in hospitals, the developed system was clinically tested. The data for heart rate (HR) and respiratory rate (RR), obtained with the developed system were compared to the same parameters obtained by the standard medical device, in order to compare their accuracy. Preliminary results from these tests are shown in this paper.